A carrier-based PWM strategy for three-level neutral-point-clamped voltage source inverters - Srirattanawichaikul,W. (2015)
This paper present a modified modulation strategy based on a triangular carrier wave for the three-level neutral-point-clamped (NPC) voltage source inverter (VSI). The switch states of each leg are determined by comparison between the modulation signals and a triangular carrier wave, which is used only of one triangular carrier wave for generate the gating pulses in three-level NPC VSI. The feasibility of the proposed modulation technique is verified by simulation and experimental results. These results show that a proposed carrier-based PWM technique can be easily implemented are provided to verify the proposed modulation strategy. © 2011 IEEE.